1993
DOI: 10.1111/j.1524-4725.1993.tb03442.x
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cell Carcinoma of the Male Nipple Case Report and Review of the Literature

Abstract: We appeal to compile all cases of BCC arising at unusual locations in order to gain a better understanding of these lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 10 publications
(15 reference statements)
2
21
0
Order By: Relevance
“…There are controversies over the incidence of BCC of the NAC. Benharroch and colleagues argued that the incidence of BCC of the NAC is higher than reported in the English literature8. However, only one case of BCC of the NAC was reported in Korean dermatological literature in 20069.…”
Section: Discussionmentioning
confidence: 96%
“…There are controversies over the incidence of BCC of the NAC. Benharroch and colleagues argued that the incidence of BCC of the NAC is higher than reported in the English literature8. However, only one case of BCC of the NAC was reported in Korean dermatological literature in 20069.…”
Section: Discussionmentioning
confidence: 96%
“…Benharroch and colleagues have postulated that the number of reported cases does not reflect the actual incidence of BCCs at this site, as not each case is reported or can be published [2, 11]. The literature search revealed that the number of reported cases of BCCs on the NAC has almost been doubled in the past decade.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical differential diagnosis of BCCs of NAC includes Paget's disease, Bowen's disease, erosive adenomatosis, and contact dermatitis when there are erythematous, scaling, or ulcerating lesions [11]. The chief clinical findings in the previously reported cases were plaques and papules, masses, erythema, oozing, exudation, edema, and eczema [4].…”
Section: Discussionmentioning
confidence: 99%
“…5 BCC has low metastatic potential. The overall rate of metastasis in BCC ranges from 0.0028 to 0.5%.…”
Section: Discussionmentioning
confidence: 99%